Biochemical and structural characterization of a novel 4‐O‐α‐l‐rhamnosyl‐β‐d‐glucuronidase from Fusarium oxysporum. (11th March 2021) - Kondo, Tatsuya; Kichijo, Miyu; Nakaya, Makoto; Takenaka, Shigeo; Arakawa, Takatoshi; Kotake, Toshihisa; Fushinobu, Shinya; Sakamoto, Tatsuji
Abstract : In this study, we have isolated the novel enzyme 4‐ O ‐α‐l ‐rhamnosyl‐β‐d ‐glucuronidase (FoBGlcA), which releases α‐l ‐rhamnosyl (1→4) glucuronic acid from gum arabic (GA), from Fusarium oxysporum 12S culture supernatant, and for the first time report an enzyme with such catalytic activity. The gene encoding FoBGlcA was cloned and expressed in Pichia pastoris . When GA was subjected to the recombinant enzyme, > 95% of the l ‐rhamnose (Rha) and d ‐glucuronic acid in the substrate were released, which indicates that almost all Rha binds to the glucuronic acid at the end of the GA side chains. The crystal structure of FoBGlcA was determined using a single‐wavelength anomalous dispersion at 1.51 Å resolution. FoBGlcA consisted of an N ‐terminal (β/α)8 ‐barrel domain and a C ‐terminal antiparallel β‐sheet domain. This configuration is characteristic of glycoside hydrolase (GH) family 79 proteins. A structural similarity search showed that FoBGlcA mostly resembled GH79 β‐d ‐glucuronidase (AcGlcA79A) of Acidobacterium capsulatum ; however, the root‐mean‐square deviation value was 3.2 Å, indicating that FoBGlcA has a high structural divergence. FoBGlcA had a low sequence identity with AcGlcA79A (19%) and differed from other GH79 β‐glucuronidases. The structures of FoBGlcA and AcGlcA79A also differed in terms of the loop structure location near subsite –2 of their catalytic sites, which may account for the unique substrate specificity of FoBGlcA. The amino acid residues involved in the catalytic activity of this enzyme were determined by evaluating the activity levels of various mutant enzymes based on the crystal structure analysis of the FoBGlcA reaction product complex. Database: Atomic coordinates and structure factors (codes 7DFQ and 7DFS ) have been deposited in the Protein Data Bank (http://wwpdb.org/ ). Abstract : We have elucidated the detailed substrate specificity and high‐resolution crystal structure of a novel enzyme, 4‐ O ‐α‐l ‐rhamnosyl‐β‐d ‐glucuronidase (FoBGlcA), which releases α‐l ‐rhamnosyl (1→4) glucuronic acid from gum arabic. Compared with bacteria GH79 β‐glucuronidase, the catalytic site of FoBGlcA showed a difference in the loop structure near subsite −2, which may explain the specific substrate specificity. The amino acid residues involved in catalysis were determined by evaluating the activity levels of mutant enzymes.